The roles of elected female members of reserved seats in union parishads : : a case study on Dhamrai upazila, Dhaka, Bangladesh (Bangladesh Journal of Public Administration, 2021)
Union Parishad (UP) is the lowest tier of the Local Government of Bangladesh which bridges between people and government to ensure people’s participation in governance system. Therefore, from the last two decades government has been emphasizing on enhancing political emancipation of women in local government. To promote female leadership in grass-root level, Ministry of Local Government established a provision in the Local Government Act of reserving 3 (three) seats for women in UPs. This reformation enabled the female leaders to be elected in the UPs by a direct vote of the people. This research intends to explore the roles played by these elected female members of the studied UPs. It was conducted following a qualitative method and interview technique. Face to face interview has been taken from 45 female members of 15 UPs in Dhamrai Upazila, Dhaka with semi structured questionnaire. The study found that most of the respondents are contributing to development related project, social safety net program, controlling early marriage and dowry, family planning and female health-related program, awareness building of hygiene and sanitation, adult literacy etc. At the same time, it is found that significant numbers of the elected female members are not conscious about their responsibilities and even though they do not have any idea about UP manual. Finally, it revealed the obstacles in their workplaces, the challenges in their families, local societies, and recommended probable measures to overcome such situations. Besides, securing female leadership and active representations in the UPs can include the backward women in the mainstream of development and decision-making process which will undoubtedly contribute enormously to women empowerment.